Aplikasi Perhitungan Indeks Prestasi Mahasiswa Menggunakan Excel dan Macro Visual Basic for Application - Rusli, Muhammad; S, Ardiana (LPPM of STIMIK ESQ, 2015)
GPA is the average value obtained by the student after completing a stage or a combination of more than one stage of learning outcomes assessment. GPA consists of a semester GPA, grade point average, and the Final Grade. Perstasi index can be calculated for each student in person before the actual results issued by the Campus. GPA calculation is very important to know the approximate value derived from each stage of learning outcomes assessment, so that students can take into account the value that should be obtained to obtain the IP had hoped. Microsoft Excel is a software that one of its functions is as a database. Contained in the Microsoft Excel Macro that can automate existing operator or function in Microsoft Excel. Moreover, in the Microsoft Excel also contained Excel Visual Basic for Application (VBA) that can be used to create application programs. This study examines the stages in the creation of index calculation application perstasi (IP) using Macros and VBA to assist students in performing simulation calculations perstasi index (IP) them.